Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/ccd.24602
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the antiscatter grid on dose and image quality in pediatric interventional cardiology X‐ray systems

Abstract: Objective: To present a methodology and experimental results to assess the influence, in terms of dose and image quality, of the antiscatter grid (AG) in a pediatric cardiology X-ray system. Method: Entrance surface air kerma and image quality, using a test object and different added thicknesses of polymethyl methacrylate (PMMA), for three different acquisition protocols, were measured with and without the AG, for fluoroscopy and cine modes. The image quality parameters, signal-to-noise ratio (SNR), highcontra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…One of these radiation reduction measures includes the low-dose acquisition technology that reduces the amount of x-ray delivered per frame, without any appreciable loss of diagnostic quality. 15,16 Despite a conspicuous paucity of studies describing the image quality on use of low-dose acquisition modalities in a cardiac catheterization laboratory, ample data from the computed tomographic literature have indicated that there is little to no loss of image quality with the use of Background-X-ray use in the catheterization laboratory is guided by the principle of as low as reasonably achievable. In accordance with this principle, we reduced the default fluoroscopic frame rate from 10 to 7.5 frames/s and increased the emphasis on the use of low-dose acquisition starting January 1, 2013.…”
mentioning
confidence: 99%
“…One of these radiation reduction measures includes the low-dose acquisition technology that reduces the amount of x-ray delivered per frame, without any appreciable loss of diagnostic quality. 15,16 Despite a conspicuous paucity of studies describing the image quality on use of low-dose acquisition modalities in a cardiac catheterization laboratory, ample data from the computed tomographic literature have indicated that there is little to no loss of image quality with the use of Background-X-ray use in the catheterization laboratory is guided by the principle of as low as reasonably achievable. In accordance with this principle, we reduced the default fluoroscopic frame rate from 10 to 7.5 frames/s and increased the emphasis on the use of low-dose acquisition starting January 1, 2013.…”
mentioning
confidence: 99%
“…Conventionally, pediatric imaging has been viewed as an opportunity to reduce patient dose by removing the antiscatter grid. The reduction of pediatric patient dose has been quantified numerous times, 7 , 13 , 16 , 17 , 18 , 19 but the loss of image quality, due to the increase in scatter (increased scatter/primary) when evaluated, was quantified with phantoms as opposed to live animal models 7 , 9 , 14 , 16 , 17 , 20 . This manuscript suggests the alternative of leaving the grid in place to preserve contrast, but lowering detector Kair setting to reduce piglet Kair/fr which reduces the piglet's dose.…”
Section: Discussionmentioning
confidence: 99%
“…Three different studies performed with phantoms simulating patients 17 , 19 , 20 were performed in interventional cardiology labs; the authors of those studies recommended the removal of the grid for small patients. Ubeda et al (20) evaluated the difference in dose and image quality with and without the grid in place for four simulated patient thicknesses of 8, 12, 18, and 24 cm. They suggested that, for a patient thickness of 8 cm, the grid could potentially be removed without noticeable loss of image quality, but it should remain in place for patient thicknesses of 12 cm and above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research performed on film-screen systems in the 1980s showed that grid removal in pediatric patients undergoing fluoroscopy results in a dose reduction of up to one-third to one half with little or no compromise of the CNR [5]. The role of grid-removal on patient radiation protection has also been recently investigated in fullfield mammography [6] and interventional pediatric cardiology [7,8].…”
Section: Introductionmentioning
confidence: 97%